Pengetahuan Dan Sikap Ibu Hamil Dalam Kunjungan Antenatal Care Di Klinik Abi Ummi DW Sarmadi Palembang: Relationship Knowledge And Attitude Pregnant Women Against Antenatal Care Visit In Klinik Abi Ummi DW Sarmadi Palembang - Erike Septa Prautami (Journal of Midwifery and Nursing, 2019)
Background Antenatal care is an important way to monitor and support and to detect health of pregnant women with normal mother normal pregnancy. The objective of this study to know the relationship of knowledge and attitudes of pregnant women against antenatal care visitin Klinik Abi Ummi DW Sarmadi Palembang. The Methods used in this research is survey analytic with the approach of “cross sectional” and sample taken with technique consecutive sampling with 64 respondent. This data collect use kuisioner and bivariat analyse with chisquare test. The result there is be significant relationship between knowledge with antenatal care visited in Klinik Abi Ummi DW Sarmadi Palembang with p value = 0,000, then significant relationship between attitude with antenatal care visited in Klinik Abi Ummi DW Sarmadi Palembang with p value = 0,000. The conclusion of this research show if there is be significant relationship between knowledge and attitude pregnant women with antenatal care.